Analisis Nilai-nilai Pendidikan Islam dalam Web Series Santri Pilihan Bunda - Zazali Juwita; Devita Andaria; Muhammad Aldiansyah; Aziza Aryati; Hengki Satrisno (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This research focuses on the Islamic educational values ​​contained in the Web Series Santri Pilihan Bunda. The type of research is library research. This research uses a qualitative approach by collecting and analyzing data sourced from the literature. The data sources in this study consist of primary and secondary data. Primary data was obtained directly through the video Web Series Santri Pilihan Bunda episodes 1-8 available on the Vidio platform. While secondary data was obtained indirectly through various relevant references that are related to the research object. The data collection method uses documentation. Data analysis uses content analysis, namely the content of character dialogues, settings, and events/incidents contained in the web series. The results of this study indicate that the Web Series Santri Pilihan Bunda episodes 1-8 contain Islamic educational values ​​that cover three main aspects. First, the value of faith education which includes Faith in Allah SWT, Faith in Angels, Faith in the books of Allah SWT, Faith in the Messengers, Faith in the Last Day, and Faith in Qada and Qadar. Second, the educational value of worship which consists of mahdhah worship and ghairu mahdhah worship. Third, the value of moral education which includes morals towards Allah SWT, morals towards Rasulullah SAW, morals towards oneself, morals towards fellow human beings, as well as morals towards nature or the environment. This research can make an academic contribution in enriching the body of Islamic education studies, especially in the context of using digital media as a means of internalizing and instilling Islamic values ​​in the learning process.